Situating Psychotheraphy with Tribal Peoples in a Sovereignty Paradigm - Consuelo E. Cavalieri (Journal for Social Action in Counseling and Psychology, 2018)
American Indian and Alaska Native (AIAN) nations have experienced profound disruptions to their lifeworlds as a result of ongoing colonialism. With striking regularity, these disruptions have violated Tribal sovereignty, impacting Tribal capacities for self-determination. The ensuing distress within Tribal communities has been marked by the intergenerational transmission of colonial traumas and losses that have been conceptualized as historical trauma, historical trauma response, historical unresolved grief, and colonial trauma response. For mental health professionals to de-colonize their work with Tribal peoples, it is necessary to imbue mental health research and practice with a sovereignty perspective that supports Tribal nations’ rights to self-determination. In a sovereignty-based paradigm, psychotherapy and research would involve critically examining colonial assumptions currently enacted in western research and psychotherapy approaches and a search for therapeutic approaches that nurture each Tribal people’s self-determined relational, knowledge, and value systems.